Understanding Aggression in Digital Environment: Relationship between Shame and Guilt and Cyber Aggression in Online Social Network - Adinugroho, Indro; Kristiani, Priska; Nurrachman, Nani (Makara Human Behavior Studies in Asia, 2022)
Violence on the internet often occurs in Indonesia due to several aspects, such as political reason and entertainment purpose. It has emerged due to the rapid digital movement, which produces numerous digital applications that can widen the connection among humans from various backgrounds. Sometimes, different values and perceptions are the factors that incinerate violence on the internet, particularly verbal violence. In this study, we apply the term cyber aggression (CA), a form of structured and unstructured behavior to harm others online, to explain this phenomenon. The emergence of this new-kind of behavior must be addressed by the government and other stakeholders in managing social and political stability that requires intergroup relation. This study aims to explain two specific predictors that can empirically understand CA from the psychological perspective, namely, moral emotions and frequency of social media usage. Result shows that one dimension of moral emotion—guilt—is a significant predictor to inhibit CA. Moreover, shame precisely encourages people to conduct CA.